Mono- and dianion of a bis(benzobuta)tetraazapentacene derivative - Ji, Lei; Hahn, Sebastian; Biegger, Philipp; Reiß, Hilmar; Han, Jie; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
A bis(benzobuta)tetraazapentacene derivative was reduced to its radical anion and its dianion, using potassium [18]crown-6 anthracenide in THF. Both reduced species were characterized by UV/Vis spectroscopy of the isolated species and by spectroelectrochemistry. Two distinct single-crystal structures of the dianion and an EPR spectrum of the radical anion were obtained. Contrary to other azaacenes, the lowest energy absorption in the UV/Vis spectrum of the dianion is redshifted in comparison to that of the neutral compound.
Gesehen am 31.10.2019
Falsche Namensform Phillip Biegger im Dokument